Herpetofauna in caves of the Estremenho Karst Massif - Marques, Ana Patrícia dos Reis (2018)
The karst landscape has among other features and peculiarities, caves and scarce water at surface. The water rare at surface can be found underground in a complex hydrological network. In Portugal, karst massifs are distributed by two major zones, Lusitanian and Algarve basins. The Estremenho karst massif is the biggest massif of the country (around 900 Km2) and most of it is covered by the Serras de Aire and Candeeiros Natural Park (PNSAC). It has more than 2,000 caves and a great variety of habitats. In this territory are present 15 amphibians and 19 reptiles species, but the knowledge of the use of caves by these animals is scarce. To fill this gap, this study aimed to map the presence and distribuition of herptofauna in caves. The major results were the presence of three species (Tarentola mauritanica; Salamandra salamandra, and Pleorodeles waltl) with report of P. waltl reproduction for the first time in Portugal. This study highlighted the need of more future works with conservation of the sites and species that they harbour in view. In addition to the scarce knowledge on the presence of herpetofauna in caves, there is no significant information about the impact of water bodies on development of some species, namely amphibians. The importance of this water bodies is due to the vulnerability of the karst system to human activities that release contaminants to the environment and that can easily reach the groundwater table and springs, spreading over large distances. Thus, the second aim of this study was to see how the selected water bodies in the sampling area affect the developmento of early stages of Hyla arborea. The results showed no difference in larvae growth nor was reported high number of anomalies or mortality. The oxidative stress responses showed statistical significant difference on lipidic peroxidation between control and one of the sites, most likely related with the level of salinity. In terms of enzimatic activity of the antioxidant enzymes there were no differences on the animals exposed to the different water bodies. The results of the analyses of the selected pesticides, although with low values, show the presence of pesticides in one of the sites. This work show that water from the sampled sites is not a threat to the amphibians, but future works are needed to conclude the water bodies state of the Estremenho massif throught the year and its impacts on biodiversity.